The effect of different patterns of digital storytelling (visual and audio) on enhancing Imaginary capabilities and Creative thinking of science studies of the second grade - Al-Jabriya, Najma Nasser Salim (Journal of Educational and Psychological Sciences, 2024)
The study aimed to measure the effect of different patterns of digital storytelling (visual and audio) on enhancing the imaginative capabilities and creative thinking skills of second-grade science students. The researcher predominantly employed a quasi-experimental design, involving 40 second-grade pupils. The pupils were divided into two groups of 20 each. One group was exposed to audio digital storytelling, while the other experienced visual digital storytelling (animation). Singer’s Scale was used to assess imaginative capabilities, and the Torrance Tests were utilized to evaluate creative thinking. The results primarily indicated that both types of digital storytelling effectively enhanced imaginative capabilities, while visual storytelling was particularly effective in fostering creative thinking. One of the key recommendations was to incorporate various forms of digital storytelling in the educational field.